Daffodils and the Green Imagination: Wordsworth Through an Ecocritical Lens - Mariwan Hasan; Shkar Hama Amin (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This paper investigates the poem “I Wandered Lonely as a Cloud” by William Wordsworth using an ecocritical approach Ecocriticism focuses on the connection between literature and nature, examines how humans are related with the ecosystem. The study explains how Wordsworth shows nature, especially the beauty of daffodils, and how this relation enhances human emotions and feelings. The poem considers the opinion of Wordsworth that nature has a superpower on the human mind to bring joy and happiness. This research also highlights Wordsworth’s use of language and imagery to bring nature to life. The personification of the daffodils gives them a sense of movement and happiness, supporting the idea that nature has its own value and role. Besides the poem insists on how remembrances of nature can make a power to offer tranquility and inspiration, even when a person is alone. This indicates that the effect of nature extends and expands even after the time of experience, shifting attitudes and feelings over time.  The research includes the scope of the study, the problem, and the hypothesis. It introduces ecocriticism, examines and explores its historical improvement, and explains its application to Romantic literature, particularly the works of William Wordsworth. Then, the research tackles the studies on the Romantic age’s ecological context, Wordsworth’s personal connection with nature, and previous scholarly interpretations of “I Wandered Lonely as a Cloud.” It also includes the research methodology and literary framework adopted in this study. An ecocritical analysis of the poem itself, pointing out crucial themes, poetic devices, and the ecological messages implied in the text are pinpointed. Finally, this paper deals with these sections along with the conclusions and the works cited page, providing an inclusive view of how literature, especially Romantic poetry is able